PENGARUH UPAH KERJA TERHADAP KINERJA KARYAWAN PADA YAYASAN INSAN MEGA MULIA BREBES - Muhamad Agus Teguh Herlambang (Bajang Institute, 2023)
Human resources play an important role in a company, because the human factor (employees) is the prime mover in every activity within the company, because employees carry out company activities from planning, implementing, to controlling every activity and activity of the company. This study aims to determine the effect of wages on employee performance at the Insan Mega Mulia Brebes Foundation. The research conducted was descriptive quantitative research. The population in this study were employees who worked at the Insan Mega Mulia Brebes Foundation. Sampling using saturated sampling technique, with a total sample of 18 respondents. The data collection method in this study used a questionnaire. The method of data analysis in this study uses descriptive statistics using scores, percentages, and tables. Based on the analysis that has been done, it can be concluded that wages have an effect on employee performance. This can be seen from the average percentage of the wage variable as much as 85% positive response and the employee performance variable as much as 97% positive response given by respondents. This shows that the better the level of remuneration by the company, the better the level of employee performance. The results of this study indicate that wages affect employee performance.